THE WRITING AND SUPERVISION OF BRIGHT ENGLISH TEXTBOOK DEVELOPMENT FOR PRIMARY SCHOOL TEACHERS IN INDONESIAN CONTEXT - Nina Inayati; Erlyna Abidasari; Kharisma Naidi W.S. (Englisia: Journal of Language, Education, and Humanities, 2019)
Although English Language subject is no longer compulsory for primary school level in Indonesia based on the current Curriculum 2013, some regions still consider it essential for their area development and thus making it a compulsory local content subject—Batu Municipality is one of them. Therefore, more efforts are needed to assist English teachers as resources for teaching English is limited due to the lack of support from the national policy level, thus the reasoning for the current project. This paper aims to describe the process of writing and supervising of Bright English Textbook, which is a specifically targeted English textbook for primary schools in Batu, East Java, Indonesia. Qualitative descriptive method was used in this study, involving four primary school teachers as the subjects in the collaborative textbook writing project. The finding presents the step-by-step process from the description during the training process, the actual writing process, until the illustration and lay-outing process. Besides, it also describes the supervision process as well as the problems and solutions related to it. Some highlights and implications of the study are also discussed, with suggestions offered in the form of combined online and face-to-face supervision process and sufficient writing and publication ethics training provided before the writing process begins. It is expected that this study could benefit other teachers and researchers who want to embark on a collaborative textbook writing process to improve their project effectiveness.